2012
DOI: 10.2478/v10181-012-0095-2
|View full text |Cite
|
Sign up to set email alerts
|

Blood dendritic cells in cattle infected with bovine leukemia virus (BLV): isolation and phenotyping

Abstract: Dendritic cells (DCs) are most potent antigen presenting cells (APCs) with unique ability to prime effective immune responses. They express higher levels of MHC class II and accesory molecules on their surface, than other professional APCs. The investigations were performed on DCs generated from blood with the use of microbeads magnetically labeled with mouse anti human CD14. Flow cytometry was applied for determination of DCs immunophenotype in healthy and naturally infected with BLV cattle. For immunophenoty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 42 publications
1
3
0
Order By: Relevance
“…Interleukin 6 induces haematopoietic cell proliferation, functional maturation and differentiation, and deficiency of IL-6 can affect BMSC function and impair haematopoietic differentiation and supportive activity. In our investigations, low levels of IL-6 secretion were found in cell cultures of bone marrow-and spleen-originated BLV-infected stem cells, which is in agreement with other authors' findings and indicative of the stemness of these bone marrow and spleen cells when infected with BLV (31). Contrastingly, IL-6 secretion was higher in the blood and lymph node stem cells.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Interleukin 6 induces haematopoietic cell proliferation, functional maturation and differentiation, and deficiency of IL-6 can affect BMSC function and impair haematopoietic differentiation and supportive activity. In our investigations, low levels of IL-6 secretion were found in cell cultures of bone marrow-and spleen-originated BLV-infected stem cells, which is in agreement with other authors' findings and indicative of the stemness of these bone marrow and spleen cells when infected with BLV (31). Contrastingly, IL-6 secretion was higher in the blood and lymph node stem cells.…”
Section: Discussionsupporting
confidence: 93%
“…The data reported by others indicated an increase in the secretion of IL-10 during the progression of BLV infection. Elevated concentrations of this cytokine were noted in experimentally infected sheep, and this was associated with progression of the disease (31). Interleukin 10 actively blocked BLV replication in adherent cultures of monocytes/macrophages, which suggested involvement of this cytokine in mechanisms of viral latency (11).…”
Section: Discussionmentioning
confidence: 97%
“…The methods of DC generation and cell culture were adapted from those described by Szczotka et al ( 23 ). Briefly, DCs were generated from the bovine blood monocytes.…”
Section: Methodsmentioning
confidence: 99%
“…The viraemic state is rather short and can be detected during the first days after viral infection. The detection of viral antigens is difficult because viral protein production is suppressed by cytokines, especially by interleukin (IL)-6 and IL-10 ( 20 , 23 ). These investigations indicated that BLV infection caused disease when changes occurred in host factors.…”
Section: Introductionmentioning
confidence: 99%
“…Reactivation of this enzyme in tumour cells has been observed in humans (Allsopp et al 1992, Hoos et al 1998 and in some animal species (pig, dog, and cat), so the telomerase activity has been proposed as a marker of tumour in these mammals (Varon et al 1997, Biller et al 1998,Yazawa et al 1999, Pathak et al 2000, Biller et al 2001, Nasir et al 2001, Argyle et al 2003. The high level of telomerase activity was determined in cattle infected with bovine leukaemia virus (BLV) in blood lymphocytes, sera, and supernatants of in vitro cultured dendritic cell (Szczotka et al 2009(Szczotka et al , 2011. Telomerase activity in tumour tissue and blood samples in BLV-infected cows was investigated by Suzuki et al (2008).…”
Section: Introductionmentioning
confidence: 99%